Pediatric Ischemic Stroke. Issue 2 (April 2023) - Fox, Christine
ABSTRACT: OBJECTIVE: Pediatric cerebrovascular disease is one of the leading causes of death and disability in children. Survivors of childhood stroke and their families are often left to cope with long-lasting sequelae, such as barriers to school reentry and long-term challenges in attaining independence as adults. Because childhood stroke is rare and providers may not be familiar with the disorder, this article reviews the risk factors, acute management, and sequelae of ischemic stroke in children. LATEST DEVELOPMENTS: High-quality evidence has resulted in an organized approach to emergent treatment of ischemic stroke in adults, but most front-line providers are less prepared for emergent stroke management in children. The level of evidence for reperfusion therapies in children remains low but is growing. Thrombolysis and thrombectomy are sometimes considered for hyperacute treatment of stroke in children. Readiness for pediatric stroke at regional centers should include an organized approach to pediatric stroke triage and management based on extrapolation from adult stroke trials, expert consensus, and emerging pediatric studies. ESSENTIAL POINTS: This review provides up-to-date information about ischemic stroke risk factors and management in children. Preparation for rapid stroke diagnosis and management in children may improve outcomes.